A new phytocosmetic preparation from Thymus vulgaris stimulates adipogenesis and controls skin aging process: In vitro studies and topical effects in a double-blind placebo-controlled clinical trial - Caverzan, Jeanifer; Mussi, Lilian; Sufi, Bianca; Padovani, Giovana; Nazato, Lucas; Camargo, Flavio B.; Magalhães, Wagner V.; Di Stasi, Luiz C. [UNESP] (Wiley, 2020)
Background: The use of the injectable products for soft tissue augmentation and treatment of skin aging is an uncomfortable, invasive and related to several complications, and chronic reactions, mainly after long-term application. Efforts to develop new topically active anti-aging products with fewer adverse effects are a huge challenge that should be faced. Aims: We evaluated the anti-aging effects of a phytocosmetic preparation containing Thymus vulgaris associated with lecithin (ThymLec) on the facial wrinkles, expression lines, and face oval remodeling using a double-blind placebo-controlled clinical trial and in vitro cell culture assays. Methods: A clinical trial was conducted to evaluate the effects of ThymLec 2% on the area, length, and depth of the perioral and crow's feet wrinkles, nasolabial and smile lines, as well as face oval remodeling in female volunteers using a sophisticated Bio3D Structured-light Scanner. In the in vitro studies using 3T3-L1 mouse embryonic fibroblasts, adiponectin was measured by immunoenzymatic assay, adipogenesis by the AdipoRed reagent method, and the PPAR-γ expression by RT-PCR analysis. Results: Topical treatment with ThymLec 2% reduced facial wrinkles and expression lines promoting a face oval remodeling. In the in vitro studies, ThymLec upregulated the PPAR-γ expression increasing adiponectin production and stimulating the adipogenesis process. Conclusions: The phytocosmetic preparation containing Thymus vulgaris and lecithin is an innovative and safe topical anti-aging product promoting fat tissue augmentation by adipogenesis stimulation via the upregulation of PPAR-γ expression and adiponectin production.
Keywords: adipogenesis; facial rejuvenation; PPAR-γ; thyme; wrinkles